A Case Report of an Inadvertent Placement of Tracheostomy Tube Into the Pharynx After Emergency Tracheostomy: Management of a Failed Surgical Airway. Issue 10 (15th May 2019) - Awad, Motaz; Yaghoubian, Saman
Abstract : Inadvertent placement of a tracheostomy tube through the stoma with the distal tip cephalad in the pharynx is an unusual but potentially devastating complication. Previously reported only once in the literature, its occurrence is not well known. There are several causes of ineffective ventilation after an emergency surgical airway, and an incorrectly placed tracheostomy tube is a differential diagnosis to consider. Prompt identification of this rare complication is essential because the consequences can be fatal. We present a case describing the inadvertent insertion of a tracheostomy tube into the pharynx during emergency tracheostomy and its subsequent management.